Dampak Lingkungan Kerja Fisik dan Kompensasi terhadap Kepuasan Kerja Karyawan pada PT XYZ Curug Kabupaten Tangerang - Dicky Ikhsan Rizaldi; Imbron Imbron (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This research ains to fimd out how much physical work environment and compensation affect employee job satisfaction at PT Putra Jaya Curug, both individually and together. The method used is quantitative, with all 62 employee as the research sample. Data was proccesed usimg SPSS 25 with simple linear regression, multiple limear regression, correlation tests, coefficient of determination, t-tests, and f-tests. The results show that the physical work environment has a significant effect on job satisfaction (t-value 3,038 > t-table 2.000; sig. 0.000 < 0.05). Compensation also has a significant effect (t-value 9,271 > t-table 2.000; sig. 0.000 < 0.05). Together, both factors significantly affect employee job satisfaction (F-value 128.675 > F-table 3.150; sig. 0.000 < 0.05). The R Square value of 0.813 means that the physical work environment and compensation contribute 81.3% to job satisfaction, while the renaining 18.7% is imfluenced by other factors mot studied